STATISTICAL ANALYSIS AND FORECASTS OF SOME FINANCIAL INDICATORS FROM THE AGRICULTURAL SECTOR IN ROMANIA USING THE ARIMA MODEL - Mirela Floriana GĂMAN; Ana-Maria Camelia POPESCU (Management & Marketing)
In this paper, a statistical analysis of some financial indicators in Romania for the period 1991-2023 was made. Indicators from the agricultural field were studied, such as the export and import of animals and animal products, but also of vegetable products, as well as the total import and export. Using the ARIMA method (autoregressive integrated moving average), forecasts for the period 2024-2026 were presented for all the studied indicators.